High-resolution multi-band imaging for validation and characterization of small kepler planets - Everett, Mark E.; Barclay, Thomas; Ciardi, David R.; Horch, Elliott P.; Howell, Steve B.; Crepp, Justin R.; Silva, David R. (The Astronomical Journal, 2015)
High-resolution ground-based optical speckle and near-infrared adaptive optics images are taken to search for stars in close angular proximity to host stars of candidate planets identi fied by the NASA Kepler Mission. Neighboring stars are a potential source of false positive signals. These stars also blend into Kepler light curves, affecting estimated planet properties, and are important for an understanding of planets in multiple star systems. Deep images with high angular resolution help to validate candidate planets by excluding potential background eclipsing binaries as the source of the transit signals. A study of 18 Kepler Object of Interest stars hosting a total of 28 candidate and validated planets is presented. Validation levels are determined for 18 planets against the likelihood of a false positive from a background eclipsing binary. Most of these are validated at the 99% level or higher, including five newly validated planets in two systems: Kepler-430 and Kepler-431. The stellar properties of the candidate host stars are determined by supplementing existing literature values with new spectroscopic characterizations. Close neighbors of seven of these stars are examined using multi-wavelength photometry to determine their nature and influence on the candidate planet properties. Most of the close neighbors appear to be gravitationally bound secondaries, while a few are best explained as closely co-aligned field stars. Revised planet properties are derived for each candidate and validated planet, including cases where the close neighbors are the potential host stars. © 2015. The American Astronomical Society. All rights reserved.
46 citations (Crossref) [2023-10-31] Citation Key Alias: pop00061 tex.type: [object Object]
Keywords: Binaries: visual; Planetary systems; Planets and satellites: detection; Planets and satellites: fundamental parameters; Surveys; Techniques: high angular resolution; dept.phy; peer-reviewed

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/163-960-215-288-558 tex.type: [object Object]
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic

Exoplanet characterization by proxy: A transiting 2.15 r ⊕ planet near the habitable zone of the late K dwarf Kepler-61 - Ballard, Sarah; Charbonneau, David; Fressin, Francois; Torres, Guillermo; Irwin, Jonathan; Desert, Jean-Michel; Newton, Elisabeth; Mann, Andrew W.; Ciardi, David R.; Crepp, Justin R.; Henze, Christopher E.; Bryson, Stephen T.; et al. (The Astrophysical Journal, 2013)
We present the validation and characterization of Kepler-61b: a 2.15 R ⊕ planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon a comparison with a set of spectroscopically similar stars with directly measured radii and temperatures. We apply a stellar prior drawn from the weighted mean of these properties, in tandem with the Kepler photometry, to infer a planetary radius for Kepler-61b of 2.15 ± 0.13 R ⊕ and an equilibrium temperature of 273 ± 13 K (given its period of 59.87756 ± 0.00020 days and assuming a planetary albedo of 0.3). The technique of leveraging the physical properties of nearby “proxy” stars allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had implications for the putative habitability of Kepler-61b: the planet is 10% warmer and larger than inferred from K-band spectral characterization. From the Kepler photometry, we estimate a stellar rotation period of 36 days, which implies a stellar age of >1 Gyr. We summarize the evidence for the planetary nature of the Kepler-61 transit signal, which we conclude is 30,000 times more likely to be due to a planet than a blend scenario. Finally, we discuss possible compositions for Kepler-61b with a comparison to theoretical models as well as to known exoplanets with similar radii and dynamically measured masses.
33 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/071-947-168-650-048, pop00052 tex.type: [object Object]
Keywords: dept.phy; eclipses; planetary systems; stars: individual (Kepler-61; KOI 1361; KIC 6960913)

The same frequency of planets inside and outside open clusters of stars. - Meibom, Soren; Torres, Guillermo; Fressin, Francois; Latham, David; Rowe, Jason; Ciardi, David; Bryson, Steven; Rogers, Leslie; Henze, Christopher; Janes, Kenneth; Barnes, Sydney; Marcy, Geoffrey; et al. (Nature, 2013)
: Most stars and their planets form in open clusters. Over 95 per cent of such clusters have stellar densities too low (less than a hundred stars per cubic parsec) to withstand internal and external dynamical stresses and fall apart within a few hundred million years 1. Older open clusters have survived by virtue of being richer and denser in stars (1,000 to 10,000 per cubic parsec) when they formed. Such clusters represent a stellar environment very different from the birthplace of the Sun and other planet-hosting field stars. So far more than 800 planets have been found around Sun-like stars in the field 2. The field planets are usually the size of Neptune or smaller 3,4,5. In contrast, only four planets have been found orbiting stars in open clusters 6,7,8, all with masses similar to or greater than that of Jupiter. Here we report observations of the transits of two Sun-like stars by planets smaller than Neptune in the billion-year-old open cluster NGC6811. This demonstrates that small planets can form and survive in a dense cluster environment, and implies that the frequency and properties of planets in open clusters are consistent with those of planets around field stars in the Galaxy., (C) 2013 Nature Publishing Group
84 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Jupiter; Neptune; article; astronomy; cluster analysis; dept.phy; environment; frequency analysis; planet; priority journal; simulation; sun; velocity

An Earth-Sized Planet in the Habitable Zone of a Cool Star. - Quintana, Elisa; Barclay, Thomas; Raymond, Sean; Rowe, Jason; Bolmont, Emeline; Caldwell, Douglas; Howell, Steve; Kane, Stephen; Huber, Daniel; Crepp, Justin; Lissauer, Jack; Ciardi, David; et al. (Science, 2014)
The quest for Earth-like planets is a major focus of current exoplanet research. Although planets that are Earth-sized and smaller have been detected, these planets reside in orbits that are too close to their host star to allow liquid water on their surfaces. We present the detection of Kepler-186f, a 1.11 ± 0.14 Earth-radius planet that is the outermost of five planets, all roughly Earth-sized, that transit a 0.47 ± 0.05 solar-radius star. The intensity and spectrum of the star's radiation place Kepler-186f in the stellar habitable zone, implying that if Kepler-186f has an Earth-like atmosphere and water at its surface, then some of this water is likely to be in liquid form.
189 citations (Crossref) [2023-10-31] Place: Copyright (C) 2014 by the American Association for the Advancement of Science
Keywords: Earth; Earth (Planet); Exobiology; Extraterrestrial Environment; Planets; Stars; Celestial; Water; astrobiology; astronomy; atmosphere; cosmic radiation; dept.phy; habitat use; microclimate; priority journal; review; solar system; surface property; water

Validation of small Kepler transiting planet candidates in or near the habitable zone - Torres, Guillermo; Kane, Stephen R.; Rowe, Jason F.; Batalha, Natalie M.; Henze, Christopher E.; Ciardi, David R.; Barclay, Thomas; Borucki, William J.; Buchhave, Lars A.; Crepp, Justin R.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
A main goal of NASA's Kepler Mission is to establish the frequency of potentially habitable Earth-size planets (). Relatively few such candidates identified by the mission can be confirmed to be rocky via dynamical measurement of their mass. Here we report an effort to validate 18 of them statistically using the BLENDER technique, by showing that the likelihood they are true planets is far greater than that of a false positive. Our analysis incorporates follow-up observations including high-resolution optical and near-infrared spectroscopy, high-resolution imaging, and information from the analysis of the flux centroids of the Kepler observations themselves. Although many of these candidates have been previously validated by others, the confidence levels reported typically ignore the possibility that the planet may transit a star different from the target along the same line of sight. If that were the case, a planet that appears small enough to be rocky may actually be considerably larger and therefore less interesting from the point of view of habitability. We take this into consideration here and are able to validate 15 of our candidates at a 99.73% (3σ) significance level or higher, and the other three at a slightly lower confidence. We characterize the GKM host stars using available ground-based observations and provide updated parameters for the planets, with sizes between 0.8 and 2.9 R ⊕. Seven of them (KOI-0438.02, 0463.01, 2418.01, 2626.01, 3282.01, 4036.01, and 5856.01) have a better than 50% chance of being smaller than 2 R ⊕ and being in the habitable zone of their host stars. © 2017. The American Astronomical Society. All rights reserved..
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-258-082-978-883, pop00029 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; peer-reviewed; planetary systems; stars: individual (KOI-0172.02 = Kepler-69c ...); techniques: photometric

JWST/NIRCam 4–5 μm Imaging of the Giant Planet AF Lep b - Franson, Kyle; Balmer, William O.; Bowler, Brendan P.; Pueyo, Laurent; Zhou, Yifan; Rickman, Emily; Zhang, Zhoujian; Mukherjee, Sagnick; Pearce, Tim D.; Gagliuffi, Daniella C. Bardalez; Biddle, Lauren I.; Brandt, Timothy D.; et al. (The Astrophysical Journal Letters, 2024)
With a dynamical mass of 3 M Jup, the recently discovered giant planet AF Lep b is the lowest-mass imaged planet with a direct mass measurement. Its youth and spectral type near the L/T transition make it a promising target to study the impact of clouds and atmospheric chemistry at low surface gravities. In this work, we present JWST/NIRCam imaging of AF Lep b. Across two epochs, we detect AF Lep b in F444W (4.4 μm) with signal-to-noise ratios of 9.6 and 8.7, respectively. At the planet’s separation of 320 mas during the observations, the coronagraphic throughput is ≈7%, demonstrating that NIRCam’s excellent sensitivity persists down to small separations. The F444W photometry of AF Lep b affirms the presence of disequilibrium carbon chemistry and enhanced atmospheric metallicity. These observations also place deep limits on wider-separation planets in the system, ruling out 1.1 M Jup planets beyond 15.6 au (0.″58), 1.1 M Sat planets beyond 27 au (1″), and 2.8 M Nep planets beyond 67 au (2.″5). We also present new Keck/NIRC2 imaging of AF Lep b; combining this with the two epochs of F444W photometry and previous Keck photometry provides limits on the long-term 3–5 μm variability of AF Lep b on timescales of months to years. AF Lep b is the closest-separation planet imaged with JWST to date, demonstrating that planets can be recovered well inside the nominal (50% throughput) NIRCam coronagraph inner working angle.
Keywords: dept.phy

Validation of 12 small kepler transiting planets in the habitable zone - Torres, Guillermo; Kipping, David M; Fressin, Francois; Caldwell, Douglas A; Twicken, Joseph D; Ballard, Sarah; Batalha, Natalie M; Bryson, Stephen T; Ciardi, David R; Henze, Christopher E; Howell, Steve B; Isaacson, Howard; et al. (The Astrophysical Journal, 2015)
We present an investigation of 12 candidate transiting planets from Kepler with orbital periods ranging from 34 to 207 days, selected from initial indications that they are small and potentially in the habitable zone (HZ) of their parent stars. Few of these objects are known. The expected Doppler signals are too small to confirm them by demonstrating that their masses are in the planetary regime. Here we verify their planetary nature by validating them statistically using the BLENDER technique, which simulates large numbers of false positives and compares the resulting light curves with the Kepler photometry. This analysis was supplemented with new follow-up observations (high-resolution optical and near-infrared spectroscopy, adaptive optics imaging, and speckle interferometry), as well as an analysis of the flux centroids. For 11 of them (KOI-0571.05, 1422.04, 1422.05, 2529.02, 3255.01, 3284.01, 4005.01, 4087.01, 4622.01, 4742.01, and 4745.01) we show that the likelihood they are true planets is far greater than that of a false positive, to a confidence level of 99.73% (3σ) or higher. For KOI-4427.01 the confidence level is about 99.2% (2.6σ). With our accurate characterization of the GKM host stars, the derived planetary radii range from 1.1 to 2.7 R ⊕. All 12 objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of them that have been previously validated by others, our study doubles the number of known rocky planets in the HZ. KOI-3284.01 (Kepler-438b) and KOI-4742.01 (Kepler-442b) are the planets most similar to the Earth discovered to date when considering their size and incident flux jointly. © 2015. The American Astronomical Society. All rights reserved..
94 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-512-292-095-617 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; planetary systems; stars: individual (KOI-3284 (Kepler-438); KOI-4742 (Kepler-442)); techniques: photometric

197 candidates and 104 validated planets in k2's first five fields - Crossfield, Ian J M; Ciardi, David R; Petigura, Erik A; Sinukoff, Evan; Schlieder, Joshua E; Schlieder, Joshua E; Howard, Andrew W; Beichman, Charles A; Isaacson, Howard; Dressing, Courtney D; Christiansen, Jessie L; Fulton, Benjamin J; et al. (Astrophysical Journal Supplement Series, 2016)
We present 197 planet candidates discovered using data from the first year of the NASA K2 mission (Campaigns 0-4), along with the results of an intensive program of photometric analyses, stellar spectroscopy, high-resolution imaging, and statistical validation. We distill these candidates into sets of 104 validated planets (57 in multi-planet systems), false positives, and 63 remaining candidates. Our validated systems span a range of properties, with median values of RP= 2.3 R⊕, P = 8.6 days, Teff = 5300 K, and Kp = 12.7mag. Stellar spectroscopy provides precise stellar and planetary parameters for most of these systems. We show that K2 has increased by 30% the number of small planets known to orbit moderately bright stars (1-4 R R⊕, Kp = 9-13 mag). Of particular interest are planets smaller than 2 R⊕, orbiting stars brighter than Kp = 11.5 mag, 5 receiving Earth-like irradiation levels, and several multi-planet systems - including 4 planets orbiting the M dwarf K2-72 near mean-motion resonances. By quantifying the likelihood that each candidate is a planet we demonstrate that our candidate sample has an overall false positive rate of 15%-30%, with rates substantially lower for small candidates (<2R⊕) and larger for candidates with radii >8 R⊕ and/or with P<3 days. Extrapolation of the current planetary yield suggests that K2 will discover between 500 and 1000 planets in its planned four-year mission, assuming sufficient follow-up resources are available. Efficient observing and analysis, together with an organized and coherent follow-up strategy, are essential for maximizing the efficacy of planet-validation efforts for K2, TESS, and future large-scale surveys. © 2016. The American Astronomical Society. All rights reserved.
150 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-053-995-602-624 tex.type: [object Object]
Keywords: catalogs; dept.phy; planets and satellites: fundamental parameters; planets and satellites: general; techniques: high angular resolution; techniques: photometric; techniques: spectroscopic

KEPLER-21b: A 1.6 REarth planet transiting the bright oscillating F subgiant star HD179070 - Howell, Steve B.; Rowe, Jason F.; Bryson, Stephen T.; Quinn, Samuel N.; Marcy, Geoffrey W.; Isaacson, Howard; Ciardi, David R.; Chaplin, William J.; Metcalfe, Travis S.; Monteiro, Mário J. P. F. G.; Appourchaux, Thierry; Basu, Sarbani; et al. (The Astrophysical Journal, 2012)
We present Kepler observations of the bright (V = 8.3), oscillating star HD179070. The observations show transit-like events which reveal that the star is orbited every 2.8days by a small, 1.6 R Earth object. Seismic studies of HD179070 using short cadence Kepler observations show that HD179070 has a frequency-power spectrum consistent with solar-like oscillations that are acoustic p-modes. Asteroseismic analysis provides robust values for the mass and radius of HD179070, 1.34 ± 0.06 M ⊙ and 1.86 ± 0.04 R ⊙, respectively, as well as yielding an age of 2.84 ± 0.34Gyr for this F5 subgiant. Together with ground-based follow-up observations, analysis of the Kepler light curves and image data, and blend scenario models, we conservatively show at the >99.7% confidence level (3σ) that the transit event is caused by a 1.64 0.04 R Earth exoplanet in a 2.785755 ± 0.000032day orbit. The exoplanet is only 0.04 AU away from the star and our spectroscopic observations provide an upper limit to its mass of ∼10 M Earth (2σ). HD179070 is the brightest exoplanet host star yet discovered by Kepler. © 2012. The American Astronomical Society. All rights reserved.
101 citations (Crossref) [2023-10-31] Citation Key Alias: pop00009 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: activity; stars: individual (HD 179070: KIC 3632418); stars: interiors; stars: late-type; stars: magnetic field; stars: oscillations (including pulsations); techniques: photometric